Association between childhood trauma, intimate partner violence, and perceived parental competence among women abusing amphetamine-type stimulant - Wahab, Suzaily; Sivarajah, Rubini; Azmi, Amirul Danial; Chemi, Norliza; Mahadevan, Raynuha (Frontiers in Psychiatry, 2023)
This cross-sectional study examines the correlation between childhood trauma, intimate partner violence (IPV) and parenting self-efficacy among women who reported using amphetamine-type stimulants (ATS) in an institutional drug rehabilitation center. A total of 106 participants were recruited using purposive sampling of which 88 were mothers. Questionnaires were used to collect sociodemographic data and the studied variables. Most of these women had experienced emotional abuse, sexual abuse, and physical neglect in childhood. IPV assessments revealed that 70.5% (n=74) and 30.5% (n=32) had experienced physical and sexual violence, respectively. In terms of parenting competency, they scored 79.5% for self-efficacy and 54.4% for parenting satisfaction. Childhood emotional abuse significantly increases the odds of individuals experiencing sexual violence by 20.9%. We found that childhood trauma and IPV did not have a significant relationship with the parenting efficacy. Conversely, childhood emotional and physical abuse were negatively corelated to parenting satisfaction. It is imperative that any form of childhood abuse to be recognised and stopped early to reduce the harm it brings to women later in life.